A participatory approach to embedding evidence in practice to support early language and communication in a London nursery school. (7th September 2022) - Harmey, Sinead; Ang, Lynn; Grenier, Julian
Abstract : IOE (Institute of Education), UCL's Faculty of Education and Society (University College London, UK) has a long tradition of engagement with schools to support young children's learning and co-produce knowledge through research–practice partnerships. From the first demonstration schools in the early 1900s to engagement with contemporary research schools, the vital importance of linking theory and practice in education through schools has been an integral part of the IOE's values and ethos. One way to link theory to practice is to utilise participatory research methodologies to embed evidence in practice. This article discusses the research project Manor Park Talks, undertaken in collaboration with IOE and a leading partner, a head teacher and IOE alumnus of the East London Teaching and Research School. The aim of the project was to support early language and communication in a cluster of early years settings in Newham, London, and it involved a process of co-production in the design of a systematic review to assess the evidence-based pedagogical strategies that can be used to inform teaching practices to enhance the professional development of early years education practitioners (to include teachers, classroom assistants, childcare workers and other ancillary staff). The research aimed to evaluate a community of practice for early years practitioners to support young children's early language development and communication, and to inform an evidence-based practice tool to guide teaching practices in early years settings. A commentary on the review findings and methodological innovation of the study in using a participatory approach to review the evidence is provided in this article.